2019
DOI: 10.1182/blood-2019-123747
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Therapies Following Venetoclax Discontinuation in CLL: Focus on B-Cell Receptor Signal Transduction Inhibitors and Cellular Therapies

Abstract: Introduction: Venetoclax (VEN) based therapy has become a standard of care in front line and relapsed-refractory (R/R) CLL based on favorable efficacy and toxicity. Whereas prospective data regarding activity of therapies following ibrutinib (IBR) or idelalisib (IDE) are available in the settings of progression (VEN, non-covalent BTKi) and intolerance (acalabrutinib), how best to manage patients (pts) who discontinue (dc) VEN remains a key unanswered question. With the increased use of VEN in early lines of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…11,12 Although prospective studies have demonstrated the efficacy of venetoclax postibrutinib, 13 limited data exist to inform choice of therapy postvenetoclax. [14][15][16][17][18] Here, we report the characteristics and outcomes of patients with R/R CLL who received BTKi after venetoclax discontinuation for PD.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although prospective studies have demonstrated the efficacy of venetoclax postibrutinib, 13 limited data exist to inform choice of therapy postvenetoclax. [14][15][16][17][18] Here, we report the characteristics and outcomes of patients with R/R CLL who received BTKi after venetoclax discontinuation for PD.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al [30] described ten patients with progressive CLL after venetoclax (including four cases after successful salvage of Richter transformation) treated with BTK inhibitor therapy, with objective responses in nine cases, although cohort follow up was short. Other groups have similarly reported responses to ibrutinib in small patient cohorts progressing after venetoclax therapy with limited follow up [76][77][78][79][80] . In a recent retrospective analysis of 188 patients receiving subsequent therapy after venetoclax, patients receiving BTK inhibitors had an estimated 24-month PFS of 78%, with longer disease control in BTK inhibitor naïve patients.…”
Section: Pitfallsmentioning
confidence: 97%
“…3 The largest series to date has been presented in abstract form and comes from a retrospective real-world study that included 326 patients who discontinued venetoclax. 6 A subcohort of 44 patients were BTKi naïve before treatment with venetoclax, and the ORR with subsequent BTKi therapy among these patients was 83.9%, with a median PFS of 32 months. These data are strikingly consistent with the findings of Lin et al…”
mentioning
confidence: 95%
“…The conventional explanation is that platelets with autoantibodies bound to their surface are prematurely destroyed in the spleen, liver, or both through interaction with Fcg receptors. 4 Autoantibodies can also induce complement-mediated 5 or desialylationinduced destruction of platelets, 6,7 as well as inhibit megakaryocyte function. Aged desialylated platelets are cleared via the hepatic Ashwell-Morell receptor (AMR).…”
mentioning
confidence: 99%
See 1 more Smart Citation